(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
It is the purpose of this study to examine how the MGNREGA has affected the financial situations of India’s indigenous tribal people. Established in 2005, MGNREGA seeks to improve livelihood stability by offering rural families a minimum of 100 days of pay work annually. Examining the program’s effects on the economic well-being of tribal populations—among India’s most marginalised groups—is the primary goal of this research. This study employs a mixed-methods strategy, drawing on both quantitative data culled from official reports and household surveys and qualitative insights gleaned from in-depth interviews and focus groups held throughout specific tribal areas. Income, spending habits, availability of basic services, and general livelihood security are some of the most important metrics tracked. Initial results indicate that MGNREGA has helped tribal communities economically by lowering migration, increasing access to basic services, and providing stable work. On the other hand, problems including late payments, poor implementation, and beneficiaries not knowing about their rights are also highlighted in the report. Better administration, more community involvement, and individualised interventions to meet the specific requirements of tribal communities are some of the policy suggestions made in the paper’s last section, which aims to improve MGNREGA’s performance in tribal regions. The crucial role of employment initiatives in reshaping the economic landscape of India’s tribal tribes is highlighted in this research, which intends to add to the wider conversation on rural development and social fairness.